2020
DOI: 10.1039/d0ra03307c
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of oil refinery effluent using bio-adsorbent developed from activated palm kernel shell and zeolite

Abstract: This study investigated the potential of palm kernel shell (PKS) as a biomass feed for adsorbent production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 101 publications
2
6
0
Order By: Relevance
“…CSAC had some of the pores partially blocked. Prominent bright silver patches were seen on the surface of PKCAC suggesting the presence of iron oxide which is in line with the study reported by [8]. The high porosity of PKCAC is known to increase adsorption capacity [5].…”
Section: A Characterization Of Adsorbentsupporting
confidence: 88%
See 2 more Smart Citations
“…CSAC had some of the pores partially blocked. Prominent bright silver patches were seen on the surface of PKCAC suggesting the presence of iron oxide which is in line with the study reported by [8]. The high porosity of PKCAC is known to increase adsorption capacity [5].…”
Section: A Characterization Of Adsorbentsupporting
confidence: 88%
“…This observation was also corroborated by [10]. The increase in surface area of the adsorbent and the availability of active sites are believed to be responsible for the rapid adsorption of metal ions at the beginning stage of the reaction [8].…”
Section: B Effect Of Contact Timesupporting
confidence: 53%
See 1 more Smart Citation
“…Zeolite is another commonly available commercial adsorbent. Zeolite is an inorganic substance with high porosity, wide surface area, high regeneration potential, strong acidic stability, and economics, making it a good adsorbent for OW treatment [54]. Jun et al [54] reported that zeolite is exceptional for removing organic compounds and heavy metals in wastewater.…”
Section: Commercial Adsorbentsmentioning
confidence: 99%
“…It is mostly preferred due to Yuan et al (2011) its direct application, simplicity and low processing costs (Ahmad et al 2005a,b & c;Sokker et al 2011;Izevbekhai et al 2020). Application of natural biosorbents for the removal of pollutant load in oily wastewater has been studied (Ibrahim et al 2010;Jun et al 2020). Devi et al (2012) employed low molecular weight crab shell chitosan as adsorbent for the treatment of vegetable oil mill effluent.…”
Section: Adsorption Treatment Technologymentioning
confidence: 99%